Boy with Thorn - Laurentiis, Rickey (Pitt poetry series., 2015)
In a landscape at once the brutal American South as it is the brutal mind, Boy with Thorn interrogates the genesis of all poetic creation--the imagination itself, questioning what role it plays in both our fascinations with and repulsion from a national history of racial and sexual violence. The personal and political crash into one language here, gothic as it is supple, meditating on visual art and myth, to desire, the practice of lynching and Hurricane Katrina. Always at its center, though, is the poet himself--confessing a double song of pleasure and inevitable pain.